2022
DOI: 10.3390/muscles1010001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Detraining on Muscle Strength and Hypertrophy Induced by Resistance Training: A Systematic Review

Abstract: A detraining period after resistance training causes a significant decrease in trained-induced muscular adaptations. However, it is unclear how long muscle strength and hypertrophy gains last after different detraining periods. Thus, the present systematic review with meta-analysis aimed to evaluate the chronic effects of detraining on muscle strength and hypertrophy induced by resistance training. Searches were conducted on PubMed, Scopus, EBSCO, CINAHL, CENTRAL, and Web of Science. The difference in means an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A meta-analysis by Bosquet et al ( 79 ) indicated that maximal force declined at a similar rate with a cessation period of <7 and 7–14 days, whilst the decrease only became significant after the third week of cessation. Whilst there is a considerable amount of literature investigating the effects of detraining on measures of muscular strength, by contrast, the effect of detraining on muscle hypertrophy is under-researched ( 80 ), especially in the short-term (i.e., <4 weeks). Peripheral adaptations, such as changes in muscle CSA and tendon properties, appear to decay faster than muscle strength and neural activation ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Bosquet et al ( 79 ) indicated that maximal force declined at a similar rate with a cessation period of <7 and 7–14 days, whilst the decrease only became significant after the third week of cessation. Whilst there is a considerable amount of literature investigating the effects of detraining on measures of muscular strength, by contrast, the effect of detraining on muscle hypertrophy is under-researched ( 80 ), especially in the short-term (i.e., <4 weeks). Peripheral adaptations, such as changes in muscle CSA and tendon properties, appear to decay faster than muscle strength and neural activation ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent article highlighted that a one-week period of no training at the midpoint of a 9-week resistance training programme negatively impacted lower body strength – but not hypertrophy, power or local muscular endurance – when compared with continuous training [ 38 ]. This suggests that the complete cessation of training might be detrimental for maximal strength where neural adaptations and exposure to load are an important antecedent to performance [ 39 ]. The periodic absence of training within a short-to-medium term programme might therefore be detrimental to some trainees, and more work might need to be done to understand optimal deloading strategies to manage training load for purposes such as maximal strength training, hypertrophy, and rapid force production – a ‘one-size fits all approach’ would appear to conflict with the emerging experiential and empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The greater afterload results in an increase in arterial pressure and more concentric remodeling of the heart. Systematic training also leads to hypertrophy of the working skeletal muscles, a change in the type of muscle fibers and an increase in dynamic strength [4].…”
Section: The Prolonged Impact Of Endurance Training On the CV Systemmentioning
confidence: 99%